### Need help from an expert?

The world’s top online tutoring provider trusted by students, parents, and schools globally.

The integral of (1+x)^3/(1+x^2) is (1/2)(1+x)^2 + (1/2)ln(1+x^2) + C.

To solve this integral, we can use the method of partial fractions. First, we write the integrand as:

(1+x)^3/(1+x^2) = (1+x)^2 + (x^2+1) - 2x^2/(1+x^2)

Next, we integrate each term separately. The first term can be integrated using the power rule:

∫(1+x)^2 dx = (1/3)(1+x)^3 + C1

The second term can be integrated using the natural logarithm:

∫(x^2+1) dx = x^3/3 + x + C2

For the third term, we use the substitution u = 1+x^2, du/dx = 2x:

∫-2x^2/(1+x^2) dx = -∫x(du/u) = -ln|1+x^2| + C3

Putting it all together, we have:

∫(1+x)^3/(1+x^2) dx = (1/3)(1+x)^3 + x^3/3 + x - ln|1+x^2| + C

Simplifying further, we get:

∫(1+x)^3/(1+x^2) dx = (1/2)(1+x)^2 + (1/2)ln(1+x^2) + C

where C = C1 + C2 + C3 is the constant of integration.

Study and Practice for Free

Trusted by 100,000+ Students Worldwide

Achieve Top Grades in your Exams with our Free Resources.

Practice Questions, Study Notes, and Past Exam Papers for all Subjects!

The world’s top online tutoring provider trusted by students, parents, and schools globally.

Loading...

Loading...